Intelligent Ureteral Stent for Early Detection of Hydronephrosis. Issue 12 (27th August 2021) - Yousefi Darestani, Mohammad Reza; Shalabi, Nabil; Lange, Dirk; Chew, Ben H.; Takahata, Kenichi
Abstract: Millions of people around the world currently suffer from kidney stone diseases. While ureteral stenting is an unmistakably effective treatment of these patients, their long‐term adverse effects can result in the build‐up of crystals around the stent. This, in turn, can lead to new ureter blockages that can dangerously increase kidney pressure, a condition known as hydronephrosis, which, if severe and prolonged, can cause irreversible kidney damage. Toward enabling early detection of hydronephrosis, this paper investigates the first intelligent ureteral stent with an integrated radiofrequency antenna and micro pressure sensor for resonance‐based wireless tracking of kidney pressure. Prototyping is conducted using a commercial ureteral stent as the substrate for microfabrication of the device. The packaged device is experimentally assessed for electrical characterizations and wireless pressure sensing using an in vitro test model. Preliminary telemetry testing demonstrates the fundamental ability of the device with its approximately linear responses of up to 1.7 kHz mmHg −1 over a pressure range of up to 120 mmHg in air, water, and artificial urine. These findings verify the efficacy of the device design and the approach to kidney pressure monitoring through indwelling stents, paving the way for the transfer of this technology to today's ureteral stent products. Abstract : An intelligent ureteral stent is reported toward enabling real‐time remote monitoring and early warning of hydronephrosis led by post‐stenting occlusion. The developed prototype based on double‐J stent is integrated with RF antenna and micro pressure sensor for wireless resonant sensing of kidney swelling. In vitro tests using artificial urine demonstrate the designed functionality of the targeted intelligent stent.